Heat Transfer at Low Temperatures - Frost, Walter; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 1975)
The purposes of this book are to provide insight and to draw attention to problems peculiar to heat transfer at low temperatures. This does not imply that the theories of classical heat transfer fail at low temperatures, but rather that many of the approximations employed in standard solutions techniques are not valid in this regime. Physical properties, for example, have more pronounced variations at low temperatures and cannot, as is conventionally done, be held constant. Fluids readily become mixtures of two or more phases and their analysis is different from that for a single-phase fluid. These and other problems which occur more frequently at low temperatures than at standard conditions are discussed in this book. Although the title specifies heat transfer, the book also contains a very comprehensive chapter on two-phase fluid flow and a partial chapter on the flow of fluids in the thermodynamically critical state. Emphasis is placed on those flow phenomena that occur at low temperatures. Flow analyses are, of course, a prerequisite to forced-convection heat transfer analyses, and thus these chapters add continuity to the text. The book is primarily written for the design engineer, but does broach many topics which should prove interesting to the researcher. For the student and teacher the book will serve as a useful reference and possibly as a text for a special topics course in heat transfer.
1: Introduction -- I. Conduction and Convection Heat Transfer -- 2: Conductive Heat Transfer -- 3: Convective Heat Transfer to Low-Temperature Fluids -- II. Two-Phase Phenomena -- 4: Terminology and Physical Description of Two-Phase Flow -- 5: Nucleate Pool Boiling -- 6: Critical Heat Flux -- 7: Film Boiling -- 8: Minimum Film Boiling Heat Flux -- 9: Vapor$1 (BLiquid Condensation on Cryogenic Surfaces -- 10: Vapor$1 (BSolid Condensation -- 11: Pressure Drop and Compressible Flow of Cryogenic Liquid$1 (BVapor Mixtures -- 12: Forced Convection Heat Transfer with Two-Phase Flow -- 13: Transient Conditions in Boiling and Two-Phase Discharge -- III. Radiation and Helium II Heat Transport -- 14: Radiative Properties -- 15: Heat Transport in Liquid Helium II.s
Keywords: Materials science; Characterization and Evaluation of Materials